Presence of Borrelia miyamotoi infection in a highly endemic area of Lyme disease - Luis A. Marcos; Kalie Smith; Kelsey Reardon; Fredric Weinbaum; Eric D. Spitzer (BMC, 2020)
Abstract A series of cases in the Northeast of the US during 2013-2015 described a new Borrelia species, Borrelia miyamotoi, which is transmitted by the same tick species that transmits Lyme disease and causes a relapsing fever-like illness. The geographic expansion of B. miyamotoi in the US also extends to other Lyme endemic areas such as the Midwestern US. Co-infections with other tick borne diseases (TBD) may contribute to the severity of the disease. On Long Island, NY, 3-5% of ticks are infected by B. miyamotoi, but little is known about the frequency of B. miyamotoi infections in humans in this particular region. The aim of this study was to perform a chart review in all patients diagnosed with B. miyamotoi infection in Stony Brook Medicine (SBM) system to describe the clinical and epidemiological features of B. miyamotoi infection in Suffolk County, NY. In a 5 year time period (2013-2017), a total of 28 cases were positive for either IgG EIA (n = 19) or PCR (n = 9). All 9 PCR-positive cases (median age: 67; range: 22-90 years) had clinical findings suggestive of acute or relapsing infection. All these patients were thought to have a TBD, prompting the healthcare provider to order the TBD panel which includes a B. miyamotoi PCR test. In conclusion, B. miyamotoi infection should be considered in the differential diagnosis for flu-like syndromes during the summer after a deer tick bite and to prevent labeling a case with Lyme disease.